Health risk factors occurring in patients benefiting from screening for early detection of colorectal cancer - Stępień, Renata B.; Zdziebło, Kazimiera; Wiraszka, Grażyna; Posłuszna, Beata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Aim of the study was to analyze the health risk factors present in patients presenting to perform colonoscopy in the context of early detection screening for colorectal cancer. Material and methods : The study group consisted of 130 patients who in the period from 02.10.2014 to 03.03.2015 was reported to Gastrological Clinic Specialist Hospital St. Luke Konskie. in order to perform a colonoscopy for early detection of colorectal cancer. The studies used diagnostic survey method using a questionnaire in the development of copyright. Results : The largest group of patients aged 61-70 years (n = 55, 42%). Familial colon cancer, 47% (n = 61) tested. Because of inflammatory bowel it healed 13% of patients. In the study group patients presented significantly more often in adverse health behaviors in terms of diet, the use of stimulants and physical activity (p < 0.001). The most important factor in determining stratification health behaviors in the study group were education (p < 0.05). Conclusions : 1. Patients performing colonoscopy for early detection of colorectal cancer characterized by high exposure to modifiable health risk factors. 2. A higher level of education determined the significantly higher incidence of positive health behaviors. 3. A family incidence of colorectal cancer is not a motivator to change adverse health behaviors.